Lateral parietal contributions to memory impairment in posterior cortical atrophy - Ahmed, S; Loane, C; Bartels, S; Zamboni, G; Mackay, C; Baker, I; Husain, M; Thompson, S; Hornberger, M; Butler, C (Elsevier, 2018)
Objective Posterior cortical atrophy (PCA) is a neurodegenerative syndrome characterised by progressive impairment in visuospatial and perceptual function. Recent findings show that memory functioning can also be compromised early in the course of disease. In this study, we investigated the neural basis of memory impairment in PCA, and hypothesised that correlations would be observed with parietal cortex rather than classic medial temporal memory structures. Methods Eighteen PCA patients, 15 typical Alzheimer's disease (tAD) patients and 21 healthy controls underwent memory testing with the Rey Auditory Verbal Learning Test (RAVLT) word list and MRI. Voxel-based morphometry (VBM) was used to identify regions in the parietal and medial temporal lobes that correlated with memory performance. Results Compared with controls, PCA patients were impaired at learning, immediate and delayed recall and recognition of the RAVLT. Learning rate and immediate recall was significantly better in PCA compared to tAD, whereas there was no difference in delayed recall. Recognition memory also was not statistically different between patient groups, but PCA patients made significantly more false positive errors than tAD patients. VBM analysis in the PCA patients revealed a significant correlation between total learning and grey matter density in the right supramarginal gyrus, right angular gyrus and left postcentral gyrus. The left post central gyrus also significantly correlated with immediate and delayed recall and with recognition memory. No correlations were detected in the medial temporal lobe. Conclusions The findings provide novel evidence that early verbal memory impairment is frequently observed in PCA, and is associated with damage to lateral parietal structures. The results have implications for the diagnosis and management of PCA.